Effect of Early Planting on Soybean Yield - E. Adee; S. Dooley (Kansas Agricultural Experiment Station Research Reports, 2022)
In an effort to increase soybean yield potential, early planting dates have been promoted as a management practice that can increase soybean yields. Early planting of soybeans can be a relative term, meaning late April/early May for some soybean producers in Kansas. For the purpose of this study, the definition of early planted soybeans is late March/early April. Theoretically, the earlier planting date could allow for more vegetative growth and absorption of more light before blooming, increasing the yield potential. With the improvement of soybean seed treatments to protect seed when emergence is slowed due to cool and wet conditions, the early planting may be a viable option. The planting dates were late March, mid-late April, and May. One of the variety/population treatments planted early yielded 6 bu/a better than the next highest yield at the mid-April planting date at Topeka. None of the other variety/population combinations yielded higher than the mid-late April planting dates at either location.
Keywords: soybean; planting date; early planting